Relative strength over investment horizons and stock returns - ZHU, Zhaobo (Institutional Knowledge at Singapore Management University, 2019)
In this article, the authors propose a simple and novel measure of relative strength over investment horizons that synthesizes short- and intermediate-term price information. The relative-strength measure compares the short-term price trend with the intermediate-term price trend. The relative strength strategy generates substantial profits, which are greater than a simple sum of traditional short-term reversal and momentum profits. The superior performance of the relative strength strategy is evident after risk adjustments for various factor models and is robust across subperiods and different market conditions. These findings seem consistent with investor conservatism and the idea that investors are slow to adjust to new information.